2022
DOI: 10.3390/nitrogen3010004
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Inorganic Nitrogen and Organic Soil Amendment Improves Nitrogen Use Efficiency While Reducing Nitrogen Runoff

Abstract: Improved nitrogen fertiliser management and increased nitrogen use efficiency (NUE) can be achieved by synchronising nitrogen (N) availability with plant uptake requirements. Organic materials in conjunction with inorganic fertilisers provide a strategy for supplying plant-available N over the growing season and reducing N loss. This study investigated whether a combined application of inorganic N with an organic soil amendment could improve nitrogen use efficiency by reducing N loss in runoff. Nitrogen runoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…The higher agronomic efficiency could be attributed to the fact that organic manure alters soil quality following its application, influencing factors such as organic matter content, soil structure, and biological activity (Tisdall and Oades, 1982;Bronick and Lal, 2005). Phillips et al (2022) reported that addition of organic material in conjuction with inorganic fertilizers increase the nitrogen use efficiency two fold by reducing runoff loses, slow release of nutrients with better synchronization with plant nutrient uptake in rye grass. Organic amendments such as humified sledge and poultry manure signifcnatly affected the N uptake and improves the nitrogen use efficiency in rice crop (Ofori et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The higher agronomic efficiency could be attributed to the fact that organic manure alters soil quality following its application, influencing factors such as organic matter content, soil structure, and biological activity (Tisdall and Oades, 1982;Bronick and Lal, 2005). Phillips et al (2022) reported that addition of organic material in conjuction with inorganic fertilizers increase the nitrogen use efficiency two fold by reducing runoff loses, slow release of nutrients with better synchronization with plant nutrient uptake in rye grass. Organic amendments such as humified sledge and poultry manure signifcnatly affected the N uptake and improves the nitrogen use efficiency in rice crop (Ofori et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…OAs encompass a wide range of products, including animal manures, biosolids, green manure and crop residues, manufacturing wastes, and composts (Goss et al, 2013; Quilty & Cattle, 2011). A major benefit of using OAs as a partial or complete substitute for synthetic N fertilizers is their potential to reduce environmental N losses (Phillips et al, 2022; Wei et al, 2021; Xia et al, 2017), owing to the typically slower supply of inorganic (mineral) N (IN) for plant uptake that is often claimed to be more synchronized with plant demands. Indeed, synchronizing the temporal supply of N with plant demands is key to maximizing the value of N inputs and minimizing environmental N losses (Crews & Peoples, 2005).…”
Section: Introductionmentioning
confidence: 99%